Selection of small business practices priorities - Osman, Nor Hasni; Jemain, Abdul Aziz (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2013)
Small business plays an important role in Malaysian business systems. This is because it contributes to the national economic growth by creating job opportunities. As job creators, small businesses must secure access to financial resources but the critical issue surrounding the survival of small businesses is their financial management. Thus, this study approaches small business specifically to examine their financial practices in doing business.This study succeeded in interviewing 185 entrepreneurs in Kedah, which are involved in five different business sectors. These businesses include food and furniture sectors in the manufacturing area; and catering, groceries, and tailoring from the trade and service area. All these businesses represent the most important small businesses that are operating in Kedah.The selection for business practice priorities was done through a fuzzy approach. This approach had been utilised in investigating the linguistic data of business practices.The results showed that updating bookkeeping records is a dominant practice among the entrepreneurs across all sectors, except for the food processing business.